Dietary factors and their influence on immunotherapy strategies in oncology: a comprehensive review - Aleksandra Golonko; Tomasz Pienkowski; Renata Swislocka; Sylwia Orzechowska; Krystian Marszalek; Lukasz Szczerbinski; Artur Hugo Swiergiel; Wlodzimierz Lewandowski (Cell Death and Disease, 2024)
Abstract Immunotherapy is emerging as a promising avenue in oncology, gaining increasing importance and offering substantial advantages when compared to chemotherapy or radiotherapy. However, in the context of immunotherapy, there is the potential for the immune system to either support or hinder the administered treatment. This review encompasses recent and pivotal studies that assess the influence of dietary elements, including vitamins, fatty acids, nutrients, small dietary molecules, dietary patterns, and caloric restriction, on the ability to modulate immune responses. Furthermore, the article underscores how these dietary factors have the potential to modify and enhance the effectiveness of anticancer immunotherapy. It emphasizes the necessity for additional research to comprehend the underlying mechanisms for optimizing the efficacy of anticancer therapy and defining dietary strategies that may reduce cancer-related morbidity and mortality. Persistent investigation in this field holds significant promise for improving cancer treatment outcomes and maximizing the benefits of immunotherapy.